2021
DOI: 10.1177/1708538120988228
|View full text |Cite
|
Sign up to set email alerts
|

The modified frailty index-11 predicts medium-term outcomes after endovascular revascularisation for chronic limb threatening ischaemia in Asian patients

Abstract: Objective The aim was to evaluate the utility of frailty, as defined by the modified Frailty Index-1 1 (mFI-11) on predicting outcomes following endovascular revascularisation in Asian patients with chronic limb-threatening ischaemia (CLTI). Methods CLTI patients who underwent endovascular revascularisation between January 2015 and March 2017 were included. Patients were retrospectively scored using the mFI-11 to categorise frailty as low, medium or high risk. Observed outcomes included 30-day complication rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…8,10 Ongoing research may provide further useful information regarding assessment of frailty, physical function and cognitive impairment, as well as other outcomes such as quality of life and durability of revascularisation, in patients with CLTI. 34 Previous research has also demonstrated associations with frailty and outcomes over ≥1 year 3,4,[35][36][37] associated with worse overall survival and AFS at two-years, adjusting for tissue loss in their multivariable model. 3 Using the critical limb ischaemia (CLI) frailty index, a novel three-item frailty score, Morisaki et al (266 patients) showed an independent association of frailty with worse overall survival and AFS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,10 Ongoing research may provide further useful information regarding assessment of frailty, physical function and cognitive impairment, as well as other outcomes such as quality of life and durability of revascularisation, in patients with CLTI. 34 Previous research has also demonstrated associations with frailty and outcomes over ≥1 year 3,4,[35][36][37] associated with worse overall survival and AFS at two-years, adjusting for tissue loss in their multivariable model. 3 Using the critical limb ischaemia (CLI) frailty index, a novel three-item frailty score, Morisaki et al (266 patients) showed an independent association of frailty with worse overall survival and AFS.…”
Section: Discussionmentioning
confidence: 99%
“…10,35,36 Soon et al (233 patients) used the modified frailty index (mFI) and also found an association of frailty with worse one-year mortality but not major amputation in CLTI. 37 However, the utility of the mFI as a frailty tool has been questioned. 10,30 Drudi et al utilised multiple frailty tools in patients undergoing revascularisation for claudication or CLTI (148 patients; 89 with CLTI).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing to the endovascular Western cohorts from the SVS VQI registry [ 5 ], the Asian CLTI patient population was more complex, presenting with a higher incidence of comorbidities (84.5% vs. 56.2% diabetics, 54.7% vs. 8.2% CKD, respectively), a higher proportion of severely diseased lesions (78.9% vs. 22.5% TASC C-D, respectively), along with a higher proportion of patients with tissue loss (78.9% vs. 27.6%, respectively). The Singaporean (SG) cohort also appeared to have more comorbidities at baseline than their Asian counterparts in Taiwan (TW) and Japan (JP) (diabetes: SG 84.5%, TW 81%, JP 68%; hypertension: SG 90.6%, TW 85%, JP 81%) [ 6 ]. Comparing to data from the 2008 REACH registry, it is also evident that PAD is presenting later within the local population (mean age in 2008: 64.4±9.8 years vs. mean age in 2019: 67.9±11.0 years) [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a few small‐scale studies have examined the effects of various frailty measures on all‐cause mortality and AFS in patients with CLTI, but none are routinely used in clinical practice. 7 , 8 , 9 , 10 Frailty scores are calculated by assessing a set of variables such as activities of daily living, cognitive assessment, muscle mass, and nutrition. 7 , 8 , 9 , 10 These are relatively cumbersome, time‐ and resource‐consuming, subject to interobserver errors, and often impractical in relatively acute settings.…”
mentioning
confidence: 99%